2017
DOI: 10.1016/j.juro.2016.09.088
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Programmed Death Ligand 1 in Penile Cancer is of Prognostic Value and Associated with HPV Status

Abstract: PD-L1 was expressed in 48% of penile carcinomas and mainly in high risk HPV negative tumors. The pattern of expression was a prognostic factor as marginal expression was associated with absent lymph node metastases and diffuse expression was associated with poor survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 28 publications
4
60
0
3
Order By: Relevance
“…Apart from PD-L1 expression, the presence of tumor-aligned T cells has also been described as predictor of response to immune checkpoint blockade therapy [34]. As > 40% of both tumor and stromal immune cells show a CD8 positivity in penile SCC, a response to immune therapy remains conceivable [31]. At present, there are several ongoing clinical trials using checkpoint inhibitors in penile cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from PD-L1 expression, the presence of tumor-aligned T cells has also been described as predictor of response to immune checkpoint blockade therapy [34]. As > 40% of both tumor and stromal immune cells show a CD8 positivity in penile SCC, a response to immune therapy remains conceivable [31]. At present, there are several ongoing clinical trials using checkpoint inhibitors in penile cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ottenhof et al 34 published an article discussing the relationship between HPV status and PD-L1 expression, and they reported that high risk HPV-negative patients tend to have positive PD-L1 expression in tumor cells. However, although it has been reported that HPV DNA can be detected in approximately half of penile cancers, the prevalence of HPV infection in penile cancer patients from Asia is relatively low with only 13.4%.…”
Section: Discussionmentioning
confidence: 99%
“…This was facilitated by PD-L1 + tumor and immune cells, and could be prevented by anti-PD-1/PD-L1 immunotherapy. 11 A recent study demonstrated that PD-L1 was a solid biomarker of productive HPV infection of the cervix, and that it was significantly upregulated in both cancer and surrounding inflammatory cells in cervical cancer compared to other gynecologic malignancies. 12 In a previous study, we examined the expression of PD-1 and PD-L1 on cervical Tcells and dendritic cells (DC), respectively, from HR-HPV(À) or HR-HPV(+) women with different CIN grades.…”
Section: Introductionmentioning
confidence: 99%